2003
DOI: 10.1074/jbc.m304478200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional, Proteomic, and Metabolic Responses to Lithium in Galactose-grown Yeast Cells

Abstract: Lithium is highly toxic to yeast when grown in galactose medium mainly because phosphoglucomutase, a key enzyme of galactose metabolism, is inhibited. We studied the global protein and gene expression profiles of Saccharomyces cerevisiae grown in galactose in different time intervals after addition of lithium. These results were related to physiological studies where both secreted and intracellular metabolites were determined. Microarray analysis showed that 664 open reading frames were down-regulated and 725 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 48 publications
8
74
0
Order By: Relevance
“…Excellent reproducibility, and the option to manipulate individual culture parameters, make chemostat cultivation very well suited to quantitative systems biology research (Bro et al, 2003;Daran-Lapujade et al, 2004;Jansen et al, 2005;Kolkman et al, 2006). In particular, chemostat cultivation enables researchers to dissect effects of specific growth rate and of other parameters.…”
Section: Discussion Chemostats Allow Proper Systems Biologymentioning
confidence: 99%
“…Excellent reproducibility, and the option to manipulate individual culture parameters, make chemostat cultivation very well suited to quantitative systems biology research (Bro et al, 2003;Daran-Lapujade et al, 2004;Jansen et al, 2005;Kolkman et al, 2006). In particular, chemostat cultivation enables researchers to dissect effects of specific growth rate and of other parameters.…”
Section: Discussion Chemostats Allow Proper Systems Biologymentioning
confidence: 99%
“…This study revealed exclusively major changes in the central carbon metabolism pathways upon changing the carbon source. In other studies, 2D gel electrophoresis was used to obtain a global view of changes in the yeast proteome as a function of stimuli in the environment, such as cadmium [45], lithium [46], H 2 O 2 [47], sorbic acid [48] and amino acid starvation [49].…”
Section: Quantification Strategies 2d-gel-based Quantificationmentioning
confidence: 99%
“…Although it has not been tested if bipolar disorder is linked to any metabolic disorder regulated by phosphoglucomutase, inhibition of this enzyme by lithium would probably lead to galactosemia and poor glycogen turnover, as has been shown in yeast (8). A recent report has shown that phosphoglucomutase activity is up-regulated in leukocytes from lithium-treated patients, even though lithium inhibits phosphoglucomutase activity in vitro (10). In the present study, we determined the distribution of phosphoglucomutase activity in erythrocytes from control, lithiumtreated and carbamazepine-treated subjects, in order to determine if differences in phosphoglucomutase activity are linked to bipolar disorder.…”
Section: Discussionmentioning
confidence: 89%
“…Inhibition of phosphoglucomutase by lithium in yeast cells has drastic effects on carbohydrate metabolism. During glucose metabolism lithium reduces the steady-state levels of UDP-glucose, resulting in a defect of glycogen and trehalose biosynthesis, while galactose metabolism is inhibited, leading to galactosemia, accumulation of galactose-1P and Glu 1-P and inhibition of fermentation (8,10). A recent report has shown that lithium treatment up-regulates phosphoglucomutase activity in various tissues of the rat and in bipolar patients, even though lithium inhibits phosphoglucomutase activity in vitro (11).…”
Section: Introductionmentioning
confidence: 99%